2019
DOI: 10.1080/00131881.2019.1660587
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of university students’ attendance

Abstract: Background: Attendance of university students at their timetabled teaching sessions is usually associated with higher levels of educational attainment (e.g. Credé, Roch & Kieszczynka, 2010). Attendance is usually considered to reflect students' level of engagement with their course and to be critical to student success; despite the potential for technological alternatives, lectures and other face-to-face sessions still tend to be the primary method of teaching at university. Purpose: Here we review studies whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 87 publications
1
38
0
Order By: Relevance
“…The kind of lecturer, required facilities and study area of the learning activity also seem to be influencing factors of attendance and can be categorised under "institutional facilities," next to scheduling. About scheduling issues, Moores et al (2019) concluded, after a review of studies exploring attendance in HE, that the timing of scheduled classes probably is an issue for some students. Our findings confirm this conclusion.…”
Section: Trip Generationmentioning
confidence: 99%
“…The kind of lecturer, required facilities and study area of the learning activity also seem to be influencing factors of attendance and can be categorised under "institutional facilities," next to scheduling. About scheduling issues, Moores et al (2019) concluded, after a review of studies exploring attendance in HE, that the timing of scheduled classes probably is an issue for some students. Our findings confirm this conclusion.…”
Section: Trip Generationmentioning
confidence: 99%
“…Shimoff and Catania (2001) report that merely recording attendance makes a difference and, as we know, that will have a beneficial effect on performance. Transparently, consistently and conveniently recording attendance should create greater awareness among students themselves (Moores et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Administering the questionnaire in class might have caused the respondents to complete the questionnaire referring to the particular course they were attending at that time when completing the questionnaire instead of looking at their class attendance in general as it relates to other courses. Also the negative effect of self-assessment questionnaire as highlighted by Moores, Birdi and Higson (2019) and Demetriou, Ozer and Essau (2015) whereby respondents tend not to tell the whole truth might have constrained this study. The results of this study are limited to only students taking accounting courses at the exclusion of non-accounting students who might have different reasons from the targeted group.…”
Section: Limitation Of the Studymentioning
confidence: 95%
“…In the words of Clair (1999 p.179) "the classroom environment that engage students, emphasizes the importance of students' contribution, and have content directly related to knowledge assessed will undoubtedly provide encouragement to students to attend regularly". Similarly, Moores, Birdi and Higson (2019) reiterated the need of making the lectures interesting and interactive with a view of encouraging attendance. In the same vein, effectiveness of teachers and using real world settings in class (Fjortoft, 2005) and offering interesting course content (Van Schalkwyk, Menkveld and Ruiters, 2010) are said to incentivize students to attend classes.…”
Section: Interventions To Improve Class Attendancementioning
confidence: 99%